Bone Metastasis as the Only Metastatic Site in a Patient with Pancreatic Cancer following Distal Pancreatectomy - Muhammad Wasif Saif; Natalie Galanina; L. Ravage-Mass; Kristin Kaley; Daniel Cornfeld; Lynne Lamb; David Chhieng (Case Reports in Medicine)
Pancreatic cancer remains a challenge both diagnostically and therapeutically. The typical sites of metastases in pancreatic cancer include the liver and peritoneum. Other less common sites are the lung, brain, kidney, and bone. Skeletal metastases are less prevalent in occurrence but contribute to significant morbidity associated with pancreatic cancer. The prevalence of osseous metastases remains unknown but has been estimated to be between 5% and 20%. The most common osseous lesions are osteolytic in nature, but the osteoblastic ones are extremely rare. Here, we report an interesting case of pancreatic adenocarcinoma with exclusive bone metastases and discuss briefly the possible pathogenesis.